'To be or not to be' located in a cluster? A descriptive meta-analysis of the firm-specific cluster effect - Nils Grashof; Dirk Fornahl (Philipps-University Marburg, Department of Geography, 2020)
In the 21st century clusters can be observed in most developed economies. However, the scientific results regarding the effect of clusters on firm performance are highly contradictive. This inconsistency in the empirical results makes it difficult to infer general conclusions about the firm-specific cluster effect, referring to the effect from being located in a cluster on firm performance, e.g. derived through the externalities within clusters. Therefore, this paper aims to reconcile the contradictory empirical findings. It investigates whether the still prevalent assumption that clusters are a beneficial location for firms is unconditionally true or whether doubts about the alleged positive effect of clusters on firm performance are justified. By conducting a descriptive meta-analysis of the empirical literature, based on four different performance variables from four separate publication databases, the study investigates the actual effect direction as well as possible moderating influences. We find evidence for a rather positive firm-specific cluster effect. However, we identify several variables from the micro-, meso- and macro-level that directly or interactively moderate the relationship between clusters and firm success. The corresponding results demonstrate, for example, that a negative firm-specific cluster effect occurs more frequently in low-tech industries than in high-tech industries. 'To be or not to be' located in a cluster is therefore not the question, but it rather depends on the specific conditions.
Keywords: L25; O31; O32; R1; 330; meta-analysis; cluster effect; firm performance